PENGARUH SELF EFFICACY TERHADAP HASIL BELAJAR MAHASISWA SEMESTER III MATA KULIAH STATISTIKA DASAR PROGRAM STUDI PENDIDIKAN VOKASIONAL DESAIN FASHION - Siregar, Yulia Pratiwi (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
This research aims to see the extent of students' confidence in themselves in improving and developing their abilities in solving each problem given in the basic statistics course. This type of research is quantitative research using secondary data sources. The population in this study were all third semester students of the Design and Fashion Vocational Education Study Program, totaling 49 people. The sampling technique in this research was to use total sampling so that the number of samples in this research was 49 people. The data analysis technique used is inferential data analysis using a one-way Product Moment correlation test. Based on the analysis of the data that has been used, a value with a strong correlation interpretation is obtained. Based on the calculated t value obtained, which is 7.51 and compared with the t table value, which is 1.678, then 7.51 > 1.678, this means that the hypothesis in this study is accepted or in other words there is a significant relationship between self-efficacy and program student learning outcomes. design and fashion vocational education studies